Effect of Child Neglect on Academic Performance of Pupils in Primary Schools of Buyanja Sub-County Rukungiri District. - Ainembabazi, Saphra (Kabale University, 2024)
The study examined the impact of child neglect on the academic performance of primary school pupils in Buyanja Sub-County, Rukungiri District. It was guided by three objectives: to investigate the causes of child neglect affecting pupils' academic performance, to identify the effects of child neglect on academic performance, and to propose solutions to combat child neglect and improve pupils' academic performance. A descriptive research design was employed, focusing on events after they occurred. Data collection methods included questionnaires, interviews, and an interview guide. The study used both qualitative and quantitative approaches, with simple random and purposive sampling applied to a sample size of 202 respondents. The findings identified several causes of child neglect, including single parenthood, lack of parental education, parental stress and overwhelm, lack of social support, inadequate welfare systems, and parental substance abuse. The effects of child neglect on pupils' academic performance included developmental issues, insecure or disorganized attachment with caregivers, physical health problems, and learning difficulties. To address these issues, the study suggested solutions such as implementing parenting education programs, improving access to mental health services, providing community support programs, strengthening early childhood education, and enhancing child welfare systems. The study concluded by emphasizing the significant causes of child neglect, such as single parenthood, inadequate parental education, and lack of social support, and called for targeted interventions to improve the academic performance of affected pupils.